Internationalization of Multinational Companies and Cognitive Differences Across Cultures: A Neuroeconomic Perspective - Cheng, Huifang; Agbanyo, George Kwame; Zhu, Tianlun; Pan, HuiHong (Frontiers in Psychology, 2022)
From a classical perspective, multinational companies (MNCs) operate based on market determinants, but recent economic discussions emphasize the central role of the human cognitive system in the decision-making process, thereby giving birth to interdisciplinary fields such as behavioral economics and neuroeconomics. While neuroeconomics is still considered an emerging field, hitherto scant studies have investigated the reflection of cultural experiences on the nervous system. Moreover, the interpretation of cultural diversity in the decision-making process, especially from a neuroeconomic perspective, has not been explored. In response, this study, aperspective research in nature, endeavors to research the neural responses to cultural diversity by contextualizing the neuroeconomic discussion within an MNC framework as one of the best multicultural settings. This study demonstrates that the internationalization process of MNCs is established on the cultural identity and integration of the executive. Through a neuroscientific lens, our findings prove that culture is a fundamental determinant of the cognitive makeup; therefore, cultural diversity in MNCs influences their decision-making process. Moreover, the performance of MNCs is driven by cultural harmonization at the executive level. Finally, the study reveals that the novel field of neuroeconomics is instrumental in identifying cultural intuitions on brain cells and the implications on economic decisions even at a corporate level. The main contribution of this study is the initiation of a multidisciplinary merge of the sociocultural and economic as well as neuroscientific fields, as a research center for MNCs’ decision-making processes.